Corn gluten hydrolysis by Alcalase: Calibration of pH-stat - Apar, Dilek Kilic; Ozbek, Belma (INST CHEMICAL ENGINEERS, 2011)
In the present study, pH-stat method was calibrated by TNBS and OPA reactions for control of hydrolysis of corn gluten by Alcalase. Hydrolysis experiments were conducted in a batch reactor at the temperature of 50 degrees C for various pH values, and at pH 7 for 40 and 60 degrees C. The calibration was characterized by good linear correlations for both methods. The mean pK values of corn gluten hydrolysates were obtained as 6.83, 6.59 and 6.36 for 40, 50 and 60 degrees C, respectively. (C) 2010 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Corn gluten; Protein; Hydrolysis; Alcalase; pH-stat; pK; Biotechnology & Applied Microbiology; Engineering; Food Science & Technology